2020
DOI: 10.18174/529441
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of fruit and vegetable consumption in urban Rwanda: results of an urban consumer study in Kigali and North-western Rwanda

Abstract: The Wageningen Centre for Development Innovation uses a Creative Commons Attribution 4.0 (Netherlands) licence for its reports. The user may copy, distribute and transmit the work and create derivative works. Third-party material that has been used in the work and to which intellectual property rights apply may not be used without prior permission of the third party concerned. The user must specify the name as stated by the author or licence holder of the work, but not in such a way as to give the impression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Despite the health benefits, the current consumption of vegetables is insufficient to meet the daily requirements of people living on cassava-based diets. 7 Raaijmakers et al 8 and Bakker et al , 9 also reported the low vegetable intake in Nigeria and Rwanda. Thus, fortifying starchy staples with leafy vegetable powder provides an effective and convenient means of ensuring vegetable consumption among the consumers.…”
Section: Introductionmentioning
confidence: 96%
“…Despite the health benefits, the current consumption of vegetables is insufficient to meet the daily requirements of people living on cassava-based diets. 7 Raaijmakers et al 8 and Bakker et al , 9 also reported the low vegetable intake in Nigeria and Rwanda. Thus, fortifying starchy staples with leafy vegetable powder provides an effective and convenient means of ensuring vegetable consumption among the consumers.…”
Section: Introductionmentioning
confidence: 96%